Respuesta :
Answer:
Use identities:
- (a + b)² = a² + 2ab + b²
- i² = -1
Simplify:
- (x + (3 + 5i))² =
- x² + 2x(3 + 5i) + (3 + 5i)² =
- x² + 6x + 10xi + 9 + 30i - 25 =
- x² + 6x + 10xi + 30i - 16
Identity used:-
[tex]\boxed{\sf (a+b)^2=a^2+b^2+2ab}[/tex]
Now
[tex]\\ \sf\longmapsto (x+(3+5i))^2[/tex]
[tex]\\ \sf\longmapsto x^2+2x(3+5i)+(3+5i)^2[/tex]
[tex]\\ \sf\longmapsto x^2+6x+10xi+3^2+2(3)(5i)+(5i)^2[/tex]
- i^2=-1
[tex]\\ \sf\longmapsto x^2+6x+10xi+9+30i-25[/tex]
[tex]\\ \sf\longmapsto x^2+6x+10xi+30i+9-25[/tex]
[tex]\\ \sf\longmapsto x^2+6x+10xi+30i-16[/tex]